Processed lateral root of Aconitum carmichaelii Debx.: A review of cardiotonic effects and cardiotoxicity on molecular mechanisms - Zhang, Jing; Li, Dan; Zhong, Dan; Zhou, Qinmei; Yin, Yanpeng; Gao, Jihai; Peng, Cheng (Frontiers in Pharmacology, 2022)
Fuzi, the lateral root of Aconitum carmichaelii Debx., is a typical traditional herbal medicine with both poison and effect, clinical use in the treatment of heart failure and other heart diseases. In this review, we searched domestic and foreign literature to sort out the molecular mechanisms of cardiotonic and cardiotoxicity of Fuzi, also including its components. The main constituents of Fuzi for cardiotonic include the total alkaloids, polysaccharide and the water-soluble alkaloids, with specific mechanisms manifested in the inhibition of myocardial fibrosis, apoptosis and autophagy, and improvement of mitochondrial energy metabolism, which involves RAAS system, PI3K/AKT, JAK/STAT, AMPK/mTOR signaling pathway, etc. It causes cardiotoxicity mainly by diester-diterpenoid alkaloids, and the toxic mechanisms include overactivation of Na+ and Ca2+ ion channels, activation of NLRP3/ ASC/ caspase-3 inflammatory pathway and mitochondria-mediated apoptosis pathway. Three clinically used preparations containing Fuzi are also used as representatives to summarize their cardiac-strengthening molecular mechanisms.